A gambling man Charles II's Restoration game - Uglow, Jennifer S. (Farrar, Straus and Giroux, 2009)
Analyzes the reign of Charles II during the first decade of the Restoration, assessing influences ranging from plague and court licentiousness to intolerance and war, in an account that describes the king's daring secret deal with his cousin, Louis XIV.